The Effect of Environmental, Social, Governance (ESG) Disclosureand Accounting Conservatism on Tax Avoidance Practices with Firm Value as a Moderating Variable - Tri Utami, Dian; Rosidi; Baridwan, Zaki (Accounting Department,, 2025)
Purpose: This research aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure and accounting conservatism on corporate tax avoidance, considering the role of company value as a moderating variable in this relationship. Methodology/approach: This research uses an explanatory quantitative approach, using panel data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Tax avoidance is measured using the Cash Effective Tax Rate (CETR). The level of ESG disclosure is measured using a content analysis index compiled from 33 Environmental, Social, and Governance indicators. Accounting conservatism is proxied by the Book-to-Market ratio, while company value is measured using the Price-to-Book Value (PBV) ratio. The analysis technique used is panel data regression with moderating variable testing. Findings: ESG disclosure has a negative, significant effect on corporate tax avoidance, whereas accounting conservatism does not. Firm value is found to strengthen the negative relationship between ESG disclosure and tax avoidance, indicating that firms with higher market values tend to show better tax compliance as sustainability transparency increases. However, company value does not moderate the relationship between accounting conservatism and tax avoidance, suggesting that accounting conservatism functions more as a technical reporting practice than as a strategy directly related to tax policy. Practical implications: This research provides practical implications for corporate management in efforts to enhance reputation and minimize tax risk through strengthening ESG disclosure and implementing accounting conservatism. Companies with high market value are expected to incorporate both aspects into their corporate governance strategy to improve tax compliance. Originality/value: This research contributes to the literature on market discipline and tax ethics by revealing the role of corporate values in enhancing the effectiveness of ESG disclosure in curbing tax avoidance, while also demonstrating the limitations of accounting conservatism in emerging markets.